Defluoridation of drinking water using fe-al mixed metal hydroxides - Telang, T.; Deosarkar, M.P.; Shetty, R.; Kamble, S.P. (Novel Water Treatment and Separation Methods: Simulation of Chemical Processes, 2017)
In this chapter, we report findings from study carried out on removal of fluoride from drinking or potable water using Fe-Al mixed metal hydroxides. For experimental analysis, the product mixed Fe-Al hydroxides was prepared by applying a co-precipitation method. The resulting metal hydroxide was thoroughly characterized using analytical tests of X-ray diffraction (XRD), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) surface area analysis. In order to characterize the equilibrium behavior of adsorbent, we study experimentally the effects of different operating parameters. The selected parameters for analysis are adsorbent loading, initial fluoride concentration, pH of the solution, and interfering ions (usually present in groundwater). The equilibrium adsorption data was later fitted for Langmuir adsorption isotherm, and experimental observations show a maximum fluoride adsorption capacity of 2.05 mg.g-1. The experimental results reveal that the adsorption dynamics follows a pseudo-second-order kinetic model.